Spectroscopic differentiation of stars within the Red Clump (2022)
In this dissertation, the spectroscopic difference between Red Giant Branch (RGB) and Red Clump (RC) stars caused by the CN I molecule is explored and a 3D "Hertzsprung-Russell space" is proposed as a way to differentiate RGB and RC stars by spectroscopic methods alone, something that has long been sought in astronomy.